Before we say goodbye - Kawaguchi, Toshikazu, 1971- (Before the coffee gets cold ;, 2023)
The regulars at the magical Cǎf Funiculi Funicula are well acquainted with its famous legend and extraordinary time-travel offer. Many patrons have reunited with old flames, made amends with estranged family and visited loved ones. But the journey is not without risks, and there are rules to follow. In the tradition of Toshikazu Kawaguchi's sensational Before the Coffee Gets Cold Series, readers will once again be introduced to a new set of visitors: the husband with something important left to say; the woman who couldn't bid her dog farewell; the woman who couldn't answer a proposal; and the daughter who drove her father away.